2016
DOI: 10.1124/jpet.116.235788
|View full text |Cite
|
Sign up to set email alerts
|

Positive Allosteric Modulation of the Muscarinic M1Receptor Improves Efficacy of Antipsychotics in Mouse Glutamatergic Deficit Models of Behavior

Abstract: Current antipsychotics are effective in treating the positive symptoms associated with schizophrenia, but they remain suboptimal in targeting cognitive dysfunction. Recent studies have suggested that positive allosteric modulation of the M 1 muscarinic acetylcholine receptor (mAChR) may provide a novel means of improving cognition. However, very little is known about the potential of combination therapies in extending coverage across schizophrenic symptom domains. This study investigated the effect of the M 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 134 publications
0
21
0
Order By: Relevance
“…Future studies are necessary to develop a better understanding of the mechanisms by which M 1 PAMs enhance cognitive function and whether allosteric modulators that display stimulus bias can be used to selectively modulate specific aspects of M 1 signaling and in vivo activity. Lastly, while these studies shed light on the different properties of structurally distinct M 1 PAMs, recent literature has shown that sub-efficacious doses of M 1 PAMs co-administered with sub-efficacious concentrations of cholinesterase inhibitors [44,45] or antipsychotics [46] can yield efficacy in animal models. However, future studies are necessary to fully evaluate the clinical implications M 1 PAMs used in conjunction with currently approved neuropsychiatric medications.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are necessary to develop a better understanding of the mechanisms by which M 1 PAMs enhance cognitive function and whether allosteric modulators that display stimulus bias can be used to selectively modulate specific aspects of M 1 signaling and in vivo activity. Lastly, while these studies shed light on the different properties of structurally distinct M 1 PAMs, recent literature has shown that sub-efficacious doses of M 1 PAMs co-administered with sub-efficacious concentrations of cholinesterase inhibitors [44,45] or antipsychotics [46] can yield efficacy in animal models. However, future studies are necessary to fully evaluate the clinical implications M 1 PAMs used in conjunction with currently approved neuropsychiatric medications.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we and others have identified highly subtype-selective positive allosteric modulators (PAMs) of the M1 receptor that avoid activation of other mAChR subtypes (see reviews (10)(11)(12)). Importantly, M1 PAMs have shown robust efficacy in enhancing cognition and rescuing cognitive deficits in preclinical animal models relevant for AD and schizophrenia (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together with multiple studies demonstrating robust effects of M 1 PAMs on other aspects of cognitive function, these studies support the exciting possibility that highly selective M 1 PAMs may provide a novel approach for reducing cognitive deficits and negative symptoms associated with changes in cortical plasticity in schizophrenia patients. Furthermore, while M 4 PAMs are likely to have more robust antipsychotic-like effects, M 1 PAMs can augment the antipsychotic-like effects of atypical antipsychotics in wild type, but not M 1 knock-out mice (Choy et al, 2016). Accordingly, M 1 PAMs either alone or in combination with current antipsychotics, have the potential to provide comprehensive relief across symptom clusters.…”
Section: Potential Utility Of Muscarinic Receptor Pams For Treatment mentioning
confidence: 99%